FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) terhadap KINERJA PEMERINTAHAN DAERAH dalam MEWUJUDKAN APARATUR PEMERINTAHAN yang BERSIH BEBAS dari KORUPSI KOLUSI NEPOTISME (KKN) - Djauhari Djauhari; Achmad Ridwan (UNISSULA, 2015)
The presence of representatives of the people in a democratic country is not to diminish the authority of the executive but should be seen as an attempt to further guarantee of thepeople’s interests in all government policies including local governments. Parliament as an institution that oversees the local regulations and the performance of local governments tosupervise the performance of local regulations and regents in creating clean government free from corruption practices. The approach method in this research is juridical empirical research methods (socio-legal-research). Empirical juridical research is non-doctrinal, empirical studies are descriptiveand has the object of a study on the behavior of people who interact with the system arising from the existing norms. The study says that implementing the oversight function of Parliament on the performance of local government in realizing that corruption-free administration in Bombana consists of: 1)Supervision of the legislation; 2) The supervision over the administration; 3) Supervision of the executive government activities; and 4) Monitoring the establishment of governance that is free of corruption. The obstacles in carrying out oversight of local government performance can be categorized obstacles that come from members of Parliament (internal factors) as wellas the resistance of the external members of parliament (external factors). Barriers to internal factors, namely: education, experience, socio-economic conditions, the work program and thesecretariat. Barriers external factors are: changes in legislation, the recruitment of political parties and public participation.